Switching Between Ultrafast Proton Vacancy and Excess Proton Transfer along a Methanol Solvent Bridge - Codescu,M-A; Kornilov,O; Nibbering,ETJ (Optica Publishing Group, 2020)
We show how ultrafast acid-base proton transfer neutralization reactions along methanol solvent bridges can be steered from a sequential methoxide to a sequential excess proton transport pathway.